Short-term integrated rehabilitation for people with newly diagnosed thoracic cancer: a multi-centre randomized controlled feasibility trial. (February 2020) - Bayly, Joanne; Fettes, Lucy; Douglas, Eleanor; Teixiera, Maria J; Peat, Nicola; Tunnard, India; Patel, Vishit; Gao, Wei; Wilcock, Andrew; Higginson, Irene J; Maddocks, Matthew
Objectives: The main objective of this study is to determine the feasibility of recruiting and retaining patients recently diagnosed with thoracic cancer to a trial of short-term integrated rehabilitation; evaluate uptake of theoretically informed components targeting physical function, symptom self-management and participation; estimate sample size requirements for an efficacy trial. Design: Parallel group randomized controlled feasibility trial. Setting: Three U.K. hospitals. Participants: Patients ⩽eight weeks of thoracic cancer diagnosis, Eastern Cooperative Oncology Group Performance Status 0–3, any cancer stage and treatment plan. Interventions: Participants randomly allocated (1:1) to short-term integrated rehabilitation and standard care or standard care alone over 30 days. Main measures: Primary: participant recruitment and retention, targeting ⩾30% of eligible patients enrolling and ⩾50% of participants reporting outcomes at 30 days. Secondary: intervention fidelity; missing data and performance of outcome measures for self-efficacy, symptoms, physical activity and health-related quality of life. Results: Of 159 eligible patients approached, 54 (34%) were recruited. A total of 44 (82%) and 39 (72%) participants reported outcomes at 30 and 60 days, respectively. Intervention fidelity was high. Rehabilitation was delivered across 3 (1–3) sessions over 32 (22–45) days (median (range)). Changes in clinical outcomes were modest but most apparent at 60 days for health-related quality of life: Functional Assessment of Cancer Therapy Lung Cancer score median (interquartile range) change 9.7 (−12.0 to 16.0) rehabilitation versus 2.3 (−15.0 to 14.5) standard care. Conclusion: A trial to examine efficacy of short-term integrated rehabilitation for people newly diagnosed with thoracic cancer is feasible. A sample of 336 participants could detect a meaningful effect on health-related quality of life as the primary outcome.